Development of a method for synthesizing an information-analytical system for assessing the level of information transmission channels protection - Shmatko, Olexander; Yevseiev, Serhii; Dudykevych, Valerii; Milevskyi, Stanislav; Solnyshkova, Svetlana; Havrylova, Alla; Shestak, Yanina; Oriekhov, Serhii; Korsunov, Serhii; Kravchenko, Serhii (Technology center PC, 2024)
The object of the study is the process of ensuring security during data transmission through information channels. To ensure high-quality indicators of information transmission channels protection, it is necessary to periodically monitor and, when detected, close possible data leakage channels. The effectiveness of measures to protect transmission channels depends on the quality of checking the presence of possible, valid or hidden, data leakage channels. A significant number of signs of information leakage complicates the control process and leads to additional economic costs for the use of control equipment. Therefore, it is necessary to develop a method of synthesis of an information-analytical system for assessing the level of transmission channels protection. It is proposed to develop such a method on the basis of determining the dependence between control signs of the presence of information leakage channels. The proposed method allows to ensure the necessary level of security. The basis of the method for synthesis of the information-analytical system for assessing the level of information transmission channels protection is the equation of the associative connection between the control features. The presence of a connection between control signs indicates the presence of information leakage channels. This is due to the loss of characteristics (for example, voltage or signal strength) of the useful information flow due to the redistribution of data during transmission. The benefit from the application of the obtained results depends on the number of discovered and, accordingly, closed channels of information leakage. Implementation of the proposed method allows to automate the process of finding a data leak in transmission channels. The given research results can be useful in the development of software for expert decision-making systems based on the formation of knowledge bases about the relationship between control features. Implementation of the obtained results will increase the reliability and security of information transmission channels.
Keywords: leakage of information; information channel; information and measurement system; information protection; threat model